2013
DOI: 10.1194/jlr.m036103
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient-dependent phosphorylation channels lipid synthesis to regulate PPARα

Abstract: This article is available online at http://www.jlr.org targeted to treat lipid disorders, diabetes, and obesity, is highly expressed in the liver. Its induction by fasting promotes lipid uptake, fatty acid ␤ -oxidation, ketogenesis, and gluconeogenesis ( 1, 2 ). Ligand binding to PPAR ␣ causes it to heterodimerize with retinoid X receptor (RXR) ␣ , allowing activation of gene transcription at peroxisome proliferator response elements (PPRE) ( 3, 4 ). Synthetic PPAR ␣ ligands, such as fi brates, used for human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…IVB). This observation indicates that the regulation of FASN by mTORC1 may not be a feature in lactating MECs as was observed in liver ( 12 ). Site-specifi c antibodies are needed to properly analyze the phosphorylation status of FASN as it pertains to enzyme activity.…”
Section: Spot14 Increases Fatty Acid Synthase Activity In Mecsmentioning
confidence: 99%
See 2 more Smart Citations
“…IVB). This observation indicates that the regulation of FASN by mTORC1 may not be a feature in lactating MECs as was observed in liver ( 12 ). Site-specifi c antibodies are needed to properly analyze the phosphorylation status of FASN as it pertains to enzyme activity.…”
Section: Spot14 Increases Fatty Acid Synthase Activity In Mecsmentioning
confidence: 99%
“…It has been reported that mTORC mediates threonine phosphorylation at positions 1029 and 1033, which negatively regulates FASN in the mouse liver ( 12 ). Currently, no commercial antibodies directed against the phosphorylated epitopes of FASN exist; its analysis requires immunoprecipitation of FASN and use of phosphorylated threonine-specifi c antibodies ( 12 ). No difference was observed in the phosphorylated enzyme responsible for releasing MCFA products from FASN during lactation ( 55 ), was maintained at the mRNA level (supplementary Fig.…”
Section: Overexpression Of Spot14 Increases Mcfa Composition Of Milk Tagmentioning
confidence: 99%
See 1 more Smart Citation
“…Do tumor cells, at least certain subtypes with definable features, rely on de novo synthesized saturated fatty acids for vital growth, proliferation, and survival functions? Currently available data support the concept that tumor cells require what can be thought of as privileged pools of fatty acids and lipids that can be satisfied only through FASN-mediated de novo palmitate synthesis [40]. The requirement for these privileged pools and the detailed function that they provide remains to be established unequivocally; this is an area deserving active investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of FASN is up-regulated in cancer cells by gene amplification and a variety of transcriptional and translational mechanisms (3)(4)(5)(6)(7). The enzymatic activity of FASN can also be modulated by phosphorylation (8). In these scenarios either FASN levels are affected or activity level is modulated.…”
mentioning
confidence: 99%